Preferowana forma życia osobistego młodych dorosłych - Ruszkiewicz, Dorota (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
The article is devoted to the issue of the forms of personal life preferred by young adults. During the research procedure, attention was paid to the following aspects: the form of personal life which the respondents would like to live in the future; if marriage is indicated, the type of wedding that young adults would like to have in the future; respondents’ attitudes towards premarital cohabitation; respondents’ opinion on the best age to get married and on the institution of marriage. The research included 204 people in early adulthood, i.e. aged 18-19. The research used the diagnostic survey method and questionnaire technique. Research results have shown that the majority of young adults want to get married in the future, including more than half in the form of a concordat. The legalisation of marriage would be preceded by premarital cohabitation lasting from one to two years. According to the high school graduates, the optimal age for marriage is between 25 and 30 years old. The respondents expressed the view that marriage has and will always be of great importance, although it is currently perceived differently than in the past.